2022
DOI: 10.1186/s12904-022-00992-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between depression and intimacy in lung cancer patients and their family caregivers

Abstract: Background Cancer impacts both patients and their family caregivers. This study aimed to explore the interdependence between depression and intimacy in lung cancer patients and their family caregivers, providing the basis for developing a patient-caregiver centered dyadic intervention. Methods This cross-sectional study recruited 182 dyads of lung cancer patients and their family caregivers using a convenient sampling. The depression subscale of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Compelled by the bonds of kinship and constrained by financial limitations, family caregivers often shoulder the exclusive responsibility for caring for their ailing relatives. This predicament is further exacerbated by the limited availability and exorbitant costs associated with formal caregiving services, particularly pronounced in South Asian countries like India [55][56][57]. Consequently, Indian family caregivers confront a dual challenge, encompassing both the daily exigencies of livelihood and the formidable task of providing care to their ailing family members [58][59][60][61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Compelled by the bonds of kinship and constrained by financial limitations, family caregivers often shoulder the exclusive responsibility for caring for their ailing relatives. This predicament is further exacerbated by the limited availability and exorbitant costs associated with formal caregiving services, particularly pronounced in South Asian countries like India [55][56][57]. Consequently, Indian family caregivers confront a dual challenge, encompassing both the daily exigencies of livelihood and the formidable task of providing care to their ailing family members [58][59][60][61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the population of this study was middle-aged and elderly patients, with many children not being around during their radiotherapy and caregivers mainly being caregivers. The study shows that the trust and cooperation between caregivers and patients in China needs to be improved, as described previously [22]. The traditional concept of family companionship in middle-aged and elderly patients is of great signi cance.…”
Section: Discussionmentioning
confidence: 63%
“…The nancial models of the U.S. health insurance and cancer care delivery systems means a cancer diagnosis brings both heightened emotional stress and nancial strain for most cancer patients and their families. Research has shown that cancer patient and family caregivers mental and physical health outcomes are interconnected (3)(4)(5)(6); there is much work that has characterized vulnerabilities and effects of nancial burden among patients and their families (2,(7)(8)(9). What is unclear is whether willingness vs. reluctance to be communicatively open about the nancial aspects of cancer care, including the impact of the disease and treatment on the employment status of caregivers and patients, is associated with changes in patient and caregiver perceptions of their family relationships.…”
Section: Introductionmentioning
confidence: 99%